INTERAKSI FUNGSI ORGAN PERSEROANTERBATAS DAN PERLINDUNGAN HUKUM PEMEGANG SAHAMMINORITAS - Nurhasanah, Siti (FIAT JUSTISIA)
Company Limited as a legal entity, provide an important role in the organs of the company. The importance of this role because of his position as an independent legal subject who has rights and obligations itself apart from the rights and duties of private owners. Interaction organ function Limited Liability Company will be detrimental to the interests of the company as a legal entity and minority shareholders in particular, where each organ in its function does not put the interests of the company as well, but based on the proximity factor the majority shareholder in the General Meeting of Shareholders (AGM) the Board of Directors and Commissioners.Â Keywords Company Limited, Minority